A Preliminary Note on the Metallography and Chemical Analysis of Silver Samples from the Mahboubian Collection, London. Issue 2 (3rd July 2018) - Faieta, Rosangela; Guida, Giuseppe; Vidale, Massimo
ABSTRACT: This is the chemico-physical examination of 13 samples collected from the early 2nd millennium BC Linear Elamite inscribed silver gunagi vessels of the Mahboubian collection (see Desset; preceding paper). Chemical composition of the silver-copper alloys as well as their physical microstructure are considered here.